The authorship of the Second Military Survey of Galicia and Austrian Silesia at the scale 1:28,800 and the consistency of sheet content based on selected examples - Ostafin, Krzysztof; Kaim, Dominik; Troll, Mateusz; Maciejowski, Wojciech (Polish Cartographical Review, 2020)
The aim of this article is to expand the understanding of the history of cartography of the lands of southern Poland under Austrian rule in the nineteenth century. The Austrian Second Military Survey, at the scale 1:28,800, was produced for the province of Galicia between 1861 and 1864 and for Austrian Silesia between 1838 and 1841. In Galicia, work on 413 sheets was led by thirteen cartographers, and the content and descriptions were prepared by 106 cartographic technicians. On the 42 sheets of the Silesia maps, two directors and 11 technicians were recorded. The military cartographers who prepared the survey of the two provinces belonged to 71 multinational units of the army of the Austrian Empire. Work with nineteenth-century maps is fraught with uncertainty about the consistency of the series, which may be reflected in the content of the maps. The consistency of map content was tested on sheets covering the Polish Carpathians for two types of features: linear (roads) and area (forests). Expanding the understanding of these maps may contribute to reducing uncertainty in their use for various environmental and socio-economic analyses.